Self-perception of generic competences of graduates of Odontology 2016-2017, of a private university, in Lima-Peru - Pachas-Barrionuevo, Flor (2019)
Objective. Evaluate the self perception of dentistry graduates regarding the achievement of generic competences at the end of professional training. Methods. Quantitative approach, descriptive design, cross-sectional study. It was applied a structured survey comprised of three dimensions to 137 graduates 2016-2017 period. Four levels of achievement of competence were established (N1, N2, N3, and N4). Results. The commitment to personal and professional development; the commitment and responsibility with the social environment and the environment, as well as the demonstration of behavior and ethical commitment were the most reported competences in level 4, with values of 83.9%, 81.8% and 79.6% respectively. 54% of the graduates considered to be in level 3 with according to the competence of solving problems with scientific rigor. The competences reported in level 2 were: communication in English in everyday situations and topics (26.3%), written communication (7.3%), use of information and communication technologies (7.3%). No graduates reported finding themselves in level 1. Conclusions. In the group and academic work dimension, the competence of TIC´ and language proficiency failed to be self-perceived as achieved in the majority of graduates at a level 4. Similarly, in the interpersonal relations dimension, the competence of both oral and written communication was not perceived as achieved at the highest level.